Perceptions of AI Driven Research Support in Select University Libraries of Tamil Nadu - Velmurugan, V. Senthur (Indian Journal of Computer Science, 2025)
Artificial Intelligence (AI) is revolutionizing the scholarly library culture at a rapid rate, especially research support services. The awareness of research support by AI among users of some universities of Tamil Nadu is the focus of this research. 100 users, such as library professionals, research scholars, and postgraduate students, were surveyed with a structured questionnaire. The levels of awareness, behavior towards using AI tools, perceived benefits, and adoption barriers were measured in the study. The results define that although a high percentage of participants are fairly to extremely familiar with AI tools, usage is committed to language enrichment tools (i.e., Grammarly), plagiarism software (i.e., Turnitin), and generative AI websites (i.e., ChatGPT). Saving time, proper citations, and enhanced academic writing were identified as the most essential advantages by the participants. Despite concerns such as no technical skills, institutional support, and ethics, they continue. The research concludes that there is great potential for AI to enhance research support in university libraries, but its uptake is more influenced by heightened awareness, training, and policy-driven programs. The research can be utilized to guide strategic planning aimed at propelling AI implementation in library services as well as academic research settings.